Princess Power: Longitudinal Associations Between Engagement With Princess Culture in Preschool and Gender Stereotypical Behavior, Body Esteem, and Hegemonic Masculinity in Early Adolescence. Issue 6 (20th July 2021) - Coyne, Sarah M.; Linder, Jennifer Ruh; Booth, McCall; Keenan‐Kroff, Savannah; Shawcroft, Jane E.; Yang, Chongming
Abstract : Princess culture is criticized for contributing to gender stereotypes and poor body esteem, however, there is little longitudinal research examining these claims. This study examines associations between engagement with princess culture during early childhood and gender stereotypes, body esteem, and adherence to hegemonic masculinity in early adolescence. Participants included 307 children (51% female, M age  = 4.83 years, 87% White) who completed questionnaires at two time points, 5 years apart. The results indicated that early engagement with princess culture was not associated with later adherence to female gender stereotypes. However, princess engagement was associated with lower adherence to norms of hegemonic masculinity and higher body esteem. Socioeconomic status and gender moderated the results. Effect sizes were small to moderate. The changing nature of Disney princesses is discussed in the context of gender development across childhood.